Mutations inhibiting KDM4B drive ALT activation in ATRX-mutated glioblastomas - M. Udugama (Nature Portfolio, 2021)
Alternative Lengthening of Telomeres (ALT) is a telomere maintenance pathway utilised in 15% of cancers that have been associated with mutations in ATRX. Here the authors reveal a functional role of histone demethylases KDM4B in regulating ALT activation.